Pembrolizumab or Placebo Plus Adjuvant Chemotherapy With or Without Radiotherapy For Newly Diagnosed, High-Risk Endometrial Cancer: Results in Mismatch Repair-Deficient Tumors - Slomovitz, Brian M.; Cibula, David; Lv, Weiguo; Ortaç, Fırat; Hietanen, Sakari; Backes, Floor; Kikuchi, Akira; Lorusso, Domenica; Dańska-Bidzińska, Anna; Samouëlian, Vanessa; Barretina-Ginesta, Maria-Pilar; Vulsteke, Christof; et al. (American Society of Clinical Oncology (ASCO), 2026)
Mismatch repair-deficient (dMMR) endometrial cancer is an inflamed phenotype with poor outcomes when meeting high-risk criteria and limited treatment options in the adjuvant setting. We report protocol-prespecified subgroup analysis of patients with dMMR tumors from the phase 3 ENGOT-en11/GOG-3053/KEYNOTE-B21 study (NCT04634877) in newly-diagnosed, high-risk endometrial cancer after surgery with curative intent. Patients were randomized to pembrolizumab 200mg or placebo (6 cycles) plus carboplatin-paclitaxel (4-6 cycles) Q3W, then pembrolizumab 400mg or placebo Q6W (6 cycles), respectively. MMR status was a stratification factor. Patients received radiotherapy at investigator discretion. Investigator-assessed disease-free survival (DFS) was a primary endpoint. No formal hypothesis testing was performed for subgroup analysis. In the intention-to-treat population, 141 patients in the pembrolizumab arm and 140 in the placebo arm had dMMR tumors. At this interim analysis, hazard ratio for DFS favored pembrolizumab (0.31; 95%CI, 0.14-0.69); median DFS was not reached in either group. Two-year DFS rates were 92.4% (95%CI, 84.4%-96.4%) and 80.2% (95%CI, 70.8%-86.9%), respectively. No new safety signals occurred. Longer-term follow-up of outcomes will be evaluated at final analysis. Preplanned subgroup analysis based on the study's stratification factors suggests that pembrolizumab plus chemotherapy improves DFS and is clinically relevant for patients with dMMR tumors in the curative-intent setting.